The HIV treatment cascade and care continuum: updates, goals, and recommendations for the future. Issue 1 (December 2016) - Kay, Emma; Batey, D.; Mugavero, Michael
Abstract The HIV care continuum is a framework that models the dynamic stages of HIV care. The continuum consists of five main steps, which, at the population level, are depicted cross-sectionally as the HIV treatment cascade. These steps include diagnosis, linkage to care (LTC), retention in care (RiC), adherence to antiretroviral therapy (ART), and viral suppression. Although the HIV treatment cascade is represented as a linear, unidirectional framework, persons living with HIV (PLWH) often experience the care continuum in a less streamlined fashion, skip steps altogether, or even exit the continuum for a period of time and regress to an earlier stage. The proportion of PLWH decreases at each successive step of the cascade, beginning with an estimated 86% who are diagnosed and dropping dramatically to approximately 30% of PLWH who are virally suppressed in the United States (US). In this current issues review, we describe each step in the cascade, discuss targeted interventions that address weak points in the continuum, review domestic and international policies that help shape and direct HIV care strategies, and conclude with recommendations and future directions for HIV providers and policymakers. While we primarily examine issues related to domestic HIV care in the US, we also discuss international applications of the continuum in order to provide broader context.